Journal of Women's Health and Gynecology 2016
DOI: 10.17303/jwhg.2016.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Risky Sexual Behaviour by Gender in Spain

Abstract: Objectives: This study examines the determinants of risky sexual behaviour by gender in Spain.Methods: Data was taken from the Spanish Health and Sexual Behaviour Survey (2003). Controlled regression results for a wide set of variables (socio-demographic characteristics, behaviour, knowledge and attitudes) were calculated and a factor analysis to group and to rank variables by explanatory power was carried out. Gender differences were analysed by means of repeated estimations by sub-samples of men and women. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…internet usage and ever forcefully had sex with anyone. More male respondents were involved in RSB when compared with female and this is in tandem with previous study 14 , 15 . This development may be due to the explorative nature of males when it comes to risk-taking in general.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…internet usage and ever forcefully had sex with anyone. More male respondents were involved in RSB when compared with female and this is in tandem with previous study 14 , 15 . This development may be due to the explorative nature of males when it comes to risk-taking in general.…”
Section: Discussionsupporting
confidence: 89%
“…This is in keeping with another research which showed that parental connectedness and monitoring are related to better sexual health as those with good parental connectedness and monitoring were less likely to engage in RSB than their counterparts 10 . This is possibly because parents have been identified as having a primary influence on young people's sexual behaviours and inadequate/ lack of parental supervision and education might well result in risky behaviours among youths and adolescent 14 . Mothers play an important role in determining/ modelling the behaviours their children engage in, most mothers spend quality time with their children compared to fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the relationship between gender and risky sexual behaviours, with males more likely to engage in risky sexual behaviours than females (Etrawati et al, 2017;Frank et al, 2008;Gil-Lacruz & Gil-Lacruz, 2016;Mahdavian & Zolala, 2017). A crosssectional study of the determinants of risky sexual behaviour among foreign-born and Swedish-born young adults by Asamoah & Agardh (2016) found gender to affect risky sexual behaviour; males were more likely to involve in non-use of condom during sex and having sex with unknown person on their first night.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%